2013
DOI: 10.1002/jpln.201200651
|View full text |Cite
|
Sign up to set email alerts
|

Physico‐chemical characterization of humic‐metal‐phosphate complexes and their potential application to the manufacture of new types of phosphate‐based fertilizers

Abstract: The aim of this review is to describe the main physicochemical characteristics of diverse types of humic‐metal‐phosphate acid complexes. The effects of these complexes on phosphorus (P) fixation in soils with different pH values and physicochemical features and on plant phosphorus uptake are also discussed. Humic‐metal‐phosphate complexes have apparent stability constants in the same range as those of metal‐humic complexes, in solutions with diverse pH and ionic‐strength values. Likewise, the molecular‐size di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 40 publications
0
62
0
8
Order By: Relevance
“…Several recent studies have characterised synthetically produced organic matter -metalphosphate complexes (Kizewski et al 2010;Erro et al 2012) and structurally similar arsenate complexes (Mikutta and Kretzschmar 2011). Interest in such ternary complexes, dubbed "super-phosphates", has been shown from agricultural chemists (e.g., Erro et al 2012;Urrutia et al 2014). The conditions under which humic-metalphosphate complexes dissociate to orthophosphate are not well defined but include ultraviolet radiation and pH decreases (Gerke and Hermann 1992;Jones et al 1993;Hens and Merckx 2001) (Fig.…”
Section: Dissociation Of Ternary P Complexes With Humicsmentioning
confidence: 99%
“…Several recent studies have characterised synthetically produced organic matter -metalphosphate complexes (Kizewski et al 2010;Erro et al 2012) and structurally similar arsenate complexes (Mikutta and Kretzschmar 2011). Interest in such ternary complexes, dubbed "super-phosphates", has been shown from agricultural chemists (e.g., Erro et al 2012;Urrutia et al 2014). The conditions under which humic-metalphosphate complexes dissociate to orthophosphate are not well defined but include ultraviolet radiation and pH decreases (Gerke and Hermann 1992;Jones et al 1993;Hens and Merckx 2001) (Fig.…”
Section: Dissociation Of Ternary P Complexes With Humicsmentioning
confidence: 99%
“…This fact suggested that RCF were able to trigger the regulation pathways involved in shoot P needs-root P uptake crosstalk (Fig. 10) [50]. As P uptake from RCF implies additional energy, plants tend to optimize P usage in shoots and minimize P uptake in roots [50].…”
Section: The Fabrication Of Humic-mineral Complexes During the Manufamentioning
confidence: 99%
“…10) [50]. As P uptake from RCF implies additional energy, plants tend to optimize P usage in shoots and minimize P uptake in roots [50].…”
Section: The Fabrication Of Humic-mineral Complexes During the Manufamentioning
confidence: 99%
See 1 more Smart Citation
“…O autor atribuiu este resultado à possível maior energia dispensada pela planta para absorver o nutriente, justificando em partes o menor ganho de massa vegetal. Pois segundo Urrutia et al (2014) os processos para descomplexação do P do fertilizante envolvem gasto de energia, levando a planta, através de respostas metabólicas a maximizar o aproveitamento do P absorvido, oque pode ainda ocasionar um menor acúmulo de matéria seca das plantas.…”
Section: Fósforo Proveniente Do Fertilizanteunclassified